2020
DOI: 10.29252/sjku.24.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Microleakage comparison of resin modified glass ionomer and OrthoMTA used as a coronal barrier in nonvital teeth bleaching

Abstract: Background and Aim: Common causes of dental discoloration include trauma, drugs, genetic defects, decay, and age. In order to correct discoloration of pulpless teeth, internal bleaching is recommended. The aim of this study was to compare microleakage of resin modified glass ionomer and OrthoMTA used as an intraorifice barrier in non-vital bleaching. Materials and Methods: In this experimental study, 36 extracted mandibular premolars were selected and randomly divided into two experimental (n = 16) and two con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies evaluating microleakage [ 37 , 38 ] and sealing ability [ 39 ] have suggested the use of MTA which had placed in the coronal area of the root canal 1 mm below the CEJ as a cervical barrier during internal bleaching. In addition, easier removal of MTA in comparison with other cervical barriers makes it a good choice [ 38 , 40 ], although there is controversy with some studies that believe MTA removal is harder [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating microleakage [ 37 , 38 ] and sealing ability [ 39 ] have suggested the use of MTA which had placed in the coronal area of the root canal 1 mm below the CEJ as a cervical barrier during internal bleaching. In addition, easier removal of MTA in comparison with other cervical barriers makes it a good choice [ 38 , 40 ], although there is controversy with some studies that believe MTA removal is harder [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…[12] Disadvantages, include, cost, discolorations, long setting time, have prompted the quest for more up to date materials. [13,14] Biodentine is a calcium silicate based material that has better handling properties than the MTA. [15] Different techniques have been utilized to quantify micro leakage and decide the nature of root canal materials.…”
Section: Introductionmentioning
confidence: 99%